Visualization of the Ca(2+)-transport system of the mitotic apparatus of sea urchin eggs with a monoclonal antibody - Petzelt, Christian (1986)
Monoclonal antibodies have been obtained to components of Ca(2+)-sequestering vesicles from the endoplasmic reticulum of HeLa cells by isolating hybridomas that were generated by the in vitro immunization of lymphocytes followed by fusion with plasmocytoma cells. One of these monoclonal antibodies specifically labels punctate structures which appear in the mitotic apparatus of sea urchin eggs at the beginning of prophase and disappear upon the completion of cytokinesis. The antibody inhibits the Ca(2+) uptake of the membrane system in vitro. It reacts with one 46-kDa protein out of the complex protein mixture from the membrane fraction. We take all this as evidence that in fact a specific Ca(2+)-transport system is part of the mitotic apparatus, that such a system is very conserved, and that it is most probably derived from the endoplasmic reticulum.